Service quality and customer satisfaction in liner shipping - Yuen, Kum Fai (2015)
Purpose – The objectives of this paper are to identify the dimensions of service quality in liner shipping and examine their effects on customer satisfaction. Methodology – The indicators of service quality in liner shipping were identified from reviewing the literature and interviewing six qualified industry practitioners. An online survey was then administered to 183 liner shippers in Singapore. Subsequently, exploratory factor analysis and regression analysis were conducted on the collected data. Findings – Service quality in liner shipping can be represented by four key quality dimensions. In descending order of their impact on customer satisfaction, they are reliability, speed, responsiveness, and value. The differentiation by time-related attributes provides greater customer satisfaction than applying cost leadership in liner shipping. Implications – The allocation of resources to market and develop a firm’s competitive advantage should mirror the priorities established in this research. In addition, the developed measurement model could serve as a reference for liner shipping firms to assess the quality of their services. Originality / Value – A parsimonious and updated set of variables can now be used to represent service quality in the liner shipping sector. The paper also identifies the key drivers of customer satisfaction in liner shipping.